KAHOOT: Electrify your class with a game-based classroom response system - Jaganathan, Mathivannan (2014)
Kahoot is a real time and fun way of game-based learning through quizzes, discussions and surveys by using any devices with a web browser. This pedagogy captivates and encourages learners to continuously participate, present and share their knowledge in a very playful, fun and enjoyable way. Typically, educators have to play their own Kahoot before and after the introduction of their topic to assess learner`s level of understanding. In the meantime, educators must provide a space to learners to create their own assessments such as quizzes and discussions on specific topics. Overall, this gaming mechanic flips the classroom and provides engagement and motivation through empowerment of learners.